A switch from canonical to noncanonical autophagy shapes B cell responses - Martinez-Martin, Nuria; Maldonado, Paula; Gasparrini, Francesca; Frederico, Bruno; Aggarwal, Shweta; Gaya, Mauro; Tsui, Carlson; Burbage, Marianne; Keppler, Selina Jessica; Montaner, Beatriz; Jefferies, Harold B. J.; Nair, Usha; et al. (Science (American Association for the Advancement of Science), 2017)
Autophagy is important in a variety of cellular and pathophysiological situations; however, its role in immune responses remains elusive. Here, we show that among B cells, germinal center (GC) cells exhibited the highest rate of autophagy during viral infection. In contrast to mechanistic target of rapamycin complex 1–dependent canonical autophagy, GC B cell autophagy occurred predominantly through a noncanonical pathway. B cell stimulation was sufficient to down-regulate canonical autophagy transiently while triggering noncanonical autophagy. Genetic ablation of WD repeat domain, phosphoinositide–interacting protein 2 in B cells alone enhanced this noncanonical autophagy, resulting in changes of mitochondrial homeostasis and alterations in GC and antibody-secreting cells. Thus, B cell activation prompts a temporal switch from canonical to noncanonical autophagy that is important in controlling B cell differentiation and fate.